Encapsulation of lipophilic polyphenols in plant-based nanoemulsions: impact of carrier oil on lipid digestion and curcumin, resveratrol and quercetin bioaccessibility. Issue 8 (25th March 2021) - Zhou, Hualu; Zheng, Bingjing; McClements, David Julian
Abstract : The gastrointestinal fate of emulsified lipophilic polyphenols depends on the nature of the carrier oil used to deliver them. Abstract : Lipophilic polyphenol compounds (LPCs) are claimed to exhibit a broad spectrum of biological activities that may improve human health and wellbeing, including antioxidant, anti-inflammatory, and anti-cancer properties. Nanoemulsion-based delivery systems have been developed to encapsulate LPCs so as to increase their food matrix compatibility, physicochemical stability, and bioavailability. LPCs vary in their structural features, including the number and position of phenolic hydroxyl, ketone, and aliphatic groups, which results in different molecular, physicochemical, and gastrointestinal properties. In this study, we examined the impact of plant-based carrier oils (coconut, sunflower, and flaxseed oils) and LPC type (curcumin, resveratrol, and quercetin) on the in vitro gastrointestinal fate of polyphenols loaded into quillaja saponin-stabilized nanoemulsions. Coconut oil contains high levels of medium-chain saturated fatty acids (MC-SFAs), sunflower oil contains high levels of long-chain monounsaturated fatty acids (LC-MUFAs), and flaxseed oil contains high levels of long-chain polyunsaturated fatty acids (LC-PUFAs). The encapsulation efficiency and gastrointestinal stability of the LPCs were slightly lower in the MC than the LC oils. Differences in the gastrointestinal stability of the three LPCs were linked to differences in their oil–water partition coefficients. Some of the LPCs inhibited lipid digestion for certain oil types. In particular, resveratrol retarded the digestion of all three oils, but it still had the highest GIT stability and bioaccessibility. This study provides valuable information about the gastrointestinal fate of LPC-loaded nanoemulsions and highlights important differences in the behavior of LPCs with different characteristics. This knowledge may facilitate the design of more effective plant-based delivery systems for bioactive lipophilic polyphenols.